(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
In this article, an important methodological basis for the development of students’ intellectual competence is the information technology approach. They are aimed at ensuring the effectiveness of the teaching process in terms of their structure and specific characteristics, and depending on the setting of the goal, they lead to the effectiveness of the educational process. For this purpose, the use of strategies to ensure the optimization of the training process of future teachers with informational technological approaches is largely dependent on the personal and psychological characteristics of students, cognitive styles of learning, deductive and inductive methods, comparative analysis, generalization of the learned information and general conclusions was carried out.